2020
DOI: 10.1186/s12955-020-01365-5
|View full text |Cite|
|
Sign up to set email alerts
|

Health-related quality of life measured using the EQ-5D–5 L: population norms for the capital of Iran

Abstract: Objectives: EQ-5D is the most commonly used generic preference-based health-related quality of life (HRQoL) measure. The current study aimed at estimating the HRQoL index scores using EQ-5D-5 L measure in the capital of Iran; moreover, identifying some determinants of the HRQoL. Methods: A sample of 3060 subjects was selected by a stratified random sampling method from the general adult population of Tehran. Face-to-face interview was conducted to fill out the questionnaire, in this cross-sectional survey. EQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 29 publications
7
41
2
Order By: Relevance
“…Although we did not nd a signi cant relationship between gender and utility score, some studies in Portugal and Iran have reported a signi cant relationship between women and a low utility score [22,28]. However, Ping et al [5] and Vu et al [29] did not nd a signi cant relationship between utility score and gender.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Although we did not nd a signi cant relationship between gender and utility score, some studies in Portugal and Iran have reported a signi cant relationship between women and a low utility score [22,28]. However, Ping et al [5] and Vu et al [29] did not nd a signi cant relationship between utility score and gender.…”
Section: Discussioncontrasting
confidence: 88%
“…The mean of the EQ-5D Index of participants was obtained to be 0.80. This result is almost similar to the score (0.79) of the general population of Iran (using the Cross Walk method) before the Covid-19 pandemic [22]. And it was lower than the score reported in studies conducted before the Covid-19 pandemic in South Australia of 0.91 [23], Germany 0.92 [24], Poland 0.89 [25], Uruguay 0.95 [26], Italy 0.92 [27], and studies conducted during the Covid-19 epidemic in China 0.949 [5], Portugal 0.86 [28] and Vietnam 0.95 [29].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The EQ-VAS reference data can often yield a table of mean(s)/median(s) EQ-VAS scores by age-sex groups, while the mean(s)/median(s) EQ-5D-5L indexes were derived from the national value set for the EQ-5D-5L indexes reference data [20]. The population norms using the EQ-5D-5L were developed globally, from Western countries [21][22][23][24][25][26][27][28][29][30] to Asian countries [31][32][33][34][35][36][37]. A hint of population norms using the EQ-5D-5L for the Vietnamese has been done elsewhere, but the study included an urban population only, and furthermore, used Thai preferences [37].…”
Section: Introductionmentioning
confidence: 99%
“…There are several instruments for measuring HRQoL. Some are disease-speci c (e.g., St George's asthma quality of life scale, NEWQOL-6D, EORTC QOL-30), while some are generic (e.g., EQ-5D, SF-6D, WHOQOL) [14].…”
Section: Introductionmentioning
confidence: 99%